Efficacy and Safety of Ivermectin and Hydroxychloroquine in Patients with Severe COVID-19: A Randomized Controlled Trial - Jose Lenin Beltran Gonzalez; Mario González Gámez; Emanuel Antonio Mendoza Enciso; Ramiro Josue Esparza Maldonado; Daniel Hernández Palacios; Samuel Dueñas Campos; Itzel Ovalle Robles; Mariana Jocelyn Macías Guzmán; Andrea Lucia García Díaz; César Mauricio Gutiérrez Peña; Lucila Martinez Medina; Victor Antonio Monroy Colin; et al. (Infectious Disease Reports, 2022)
During the first year of the COVID-19 pandemic, unauthorized drugs were widely used. Ivermectin and hydroxychloroquine are drugs that inhibit viral replication in vitro and that have been used in several medical centers. This clinical trial analyzes their efficacy in hospitalized patients with moderate COVID-19. Methods: This a controlled, clinical, randomized, double-blind trial that included hospitalized patients with COVID-19-induced pneumonia, without severe respiratory failure. Patients were randomized to one of three groups: Group 1—hydroxychloroquine, 400 mg every 12 h on the first day and, subsequently, 200 mg every 12 h for 4 days; Group 2—ivermectin, 12 mg or 18 mg, according to patient weight; and Group 3—placebo. At inclusion, blood samples for arterial blood gases and biochemical markers were obtained. The primary outcome was established as the length of stay due to patient improvement and the rate of respiratory deterioration or death. Results: During the month of August 2020, the admission of patients requiring hospitalization mostly encompassed cases with severe respiratory failure, so we ended the recruitment process and analyzed the data that was available at the time. One hundred and six (106) patients with an average age of 53 yrs (±16.9) were included, with a greater proportion of males (n = 66, 62.2%). Seventy-two percent (72%) (n = 76) had an associated comorbidity. Ninety percent (90%) of patients were discharged due to improvement (n = 96). The average duration of hospitalization was 6 days (IQR, 3–10). No difference in hospitalization duration was found between the treatment groups (Group1: 7 vs. Group 2: 6 vs. Group 3: 5, p = 0.43) nor in respiratory deterioration or death (Group 1: 18% vs. Group 2: 22.2% vs. Group 3: 24.3%, p = 0.83). Conclusions: In non-critical hospitalized patients with COVID-19 pneumonia, neither ivermectin nor hydroxychloroquine decreases the number of in-hospital days, respiratory deterioration, or deaths.